Development of a nano‐particle‐assisted PCR assay for detection of duck tembusu virus. (9th December 2015) - Wanzhe, Y.; Jianuan, L.; Peng, L.; Jiguo, S.; Ligong, C.; Juxiang, L.
Abstract: Duck tembusu virus (DTMUV) has caused significant economic losses to the poultry industry in China since the spring of 2010. In this study, a nano‐PCR assay targeting E gene of DTMUV was developed and their sensitivities and specificities were investigated. Under the optimized conditions of nano‐PCR assay for detection of DTMUV, the nano‐PCR assay was 10‐fold more sensitive than a conventional PCR assay. The lower detection limit of the nano‐PCR assay was 1·8 × 10 2  copies  μ l −1 of DTMUV RNA, as no cross‐reaction was observed with other viruses. This is the first report to demonstrate the application of a nano‐PCR assay for the detection of DTMUV. The sensitive, and specific nano‐PCR assay developed in this study can be applied widely in clinical diagnosis and field surveillance of DTMUV‐infection. Significance and Impact of the Study: A nanoparticle‐assisted polymerase chain reaction (nano‐PCR) assay was developed in this study for the rapid detection of duck tembusu virus (DTMUV) with high sensitivity and specificity. This technique has potential application in both clinical diagnosis and field surveillance of DTMUV‐infection. Abstract : Significance and Impact of the Study: A nanoparticle‐assisted polymerase chain reaction (nano‐PCR) assay was developed in this study for the rapid detection of duck tembusu virus (DTMUV) with high sensitivity and specificity. This technique has potential application in both clinical diagnosis and field surveillance of DTMUV‐infection.